Are the needs of people with multiple long-term conditions being met? Evidence from the 2018 General Practice Patient Survey. Issue 11 (14th November 2020) - Rolewicz, Lucina; Keeble, Eilís; Paddison, Charlotte; Scobie, Sarah
Abstract : Objectives: To investigate individual, practice and area level variation in patient-reported unmet need among those with long-term conditions, in the context of general practice (GP) appointments and support from community-based services in England. Design: Cross-sectional study using data from 199 150 survey responses. Setting: Primary care and community-based services. Participants: Respondents to the 2018 English General Practice Patient Survey with at least one long-term condition. Primary and secondary outcome measures: The primary outcomes were the levels of unmet need in GP and local services among patients with multiple long-term conditions. Secondary outcomes were the proportion of variation explained by practice and area-level factors. Results: There was no relationship between needs being fully met in patients' last practice appointment and number of long-term conditions once sociodemographic characteristics and health status were taken into account (5+conditions−OR=1.04, 95% CI 0.99 to 1.09), but there was a relationship for having enough support from local services to manage conditions (5+conditions−OR=0.84, 95% CI 0.80 to 0.88). Patients with multimorbidity that were younger, non-white or frail were less likely to have their needs fully met, both in GP and from local services. Differences between practices and local authorities explained minimal variation in unmet need. Conclusions: Levels of unmet need are high, particularly for support from community services to manage multiple conditions. Patients who could be targeted for support include people who feel socially isolated, and those who have difficulties with their day-to-day living. Younger patients and certain ethnic groups with multimorbidity are also more likely to have unmet needs. Increased personalisation and coordination of care among these groups may help in addressing their needs.